Perancangan Program Pengelolaan Transaksi Pembelian dan Penjualan Perlengkapan Olahraga Pada Abadi Sport - Dede Nurahman; feri prasetyo; Eka Pratama (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2018)
Abstract  –  Purchasing and Sale of Goods System is a system that provides information services in the form of transaction data purchase and sale of goods and stock of goods. The existence of this information system is important. In this case, ABADI SPORT serve as a place of research, because the system of purchase and sale of goods in the place has not been well managed so that there is often a mistake in making the existing report, ineffective and efficient data storage because only archived. So as to complicate the search of data, the form of invoice is similar to causing an error in Recording, slow presentation of information required by the leadership. The method used is structured programming language and development method using waterfall model. Data collection method used is using observation method, interview, literature study. Analytical tools used are Use Case Diagram, Activity Diagram, Entity Relationship Diagram (ERD), Logical Record Structure (LRS). The software used is: NetBeans IDE 8.1, java 1.7.7, and Xampp 1.7.7. The design of this program is built in order to provide convenience in processing data purchase and sale both from purchases to suppliers and sales to customers as well as processing reports purchase and sales to be more precise and accurate. Key Word: Program Design, Purchasing and Sales Program